Role of PIWI-like 4 in modulating neuronal differentiation from human embryonal carcinoma cells - Subhramanyam, Charannya Sozheesvari (RNA Biol, 2020)
PIWI homologs constitute a subclass of the Argonaute family. Traditionally, they have been shown to associate with a specific class of small RNAs, piRNAs, to suppress transposable elements and protect genomic integrity in germ cells. Recent studies imply that PIWI proteins may also exert important biological functions in somatic contexts, including the brain. However, their exact role in neural development remains unknown. Hence we investigated whether PIWI proteins are involved in neuronal differentiation. By using an established cell model for studying neurogenesis, NTera2/D1 (NT2) cells, we found that a particular PIWI homolog, PIWIL4 was increasingly upregulated throughout the course of all-trans retinoic acid (RA)-mediated neuronal differentiation. During this process, PIWIL4 knockdown led to partial recovery of embryonic stem cell markers, while suppressing RA-induced expression of neuronal markers. Consistently, PIWIL4 overexpression further elevated their expression levels. Furthermore, co-immunoprecipitation revealed an RA-induced interaction between PIWIL4 and the H3K27me3 demethylase UTX. Chromatin immunoprecipitation showed that this interaction could be essential for the removal of H3K27me3 from the promoters of RA-inducible genes. By a similar mechanism, PIWIL4 knockdown also suppressed the expression of PTN and NLGN3, two important neuronal factors secreted to regulate glioma activity. We further noted that the conditioned medium collected from PIWIL4-silenced NT2 cells significantly reduced the proliferation of glioma cells. Thus, our data suggest a novel somatic role of PIWIL4 in modulating the expression of neuronal genes that can be further characterized to promote neuronal differentiation and to modulate the activity of glioma cells.